A scalable and efficient Web 2.0 reader platform for mashups. (1st January 2012) - Al-Haj Hassan, Osama; Al Shargabi, Bassam
Two of the icons of Web 2.0 applications are feed readers and mashup platforms. On one hand, feed readers provide end-users with updates of content of feeds they subscribe to. On the other hand, mashups are conceptually web services created by end-users and hosted by mashup platforms which empower end-users with a tool to query the web based on their personalised interests. In this paper, we combine the best of mashup readers and mashup platforms in order to design a novel Web 2.0 application called mashup reader. Mashup reader enables end-users to subscribe to their favourite mashups and obtain updates of the result of executing those mashups. In this paper, we introduce the design of mashup reader, provide ways to improve its efficiency, and evaluate its execution mechanism. Our experiments show that mashup reader is an efficient and scalable Web 2.0 platform which provides end-users with an effective web querying tool.